Educational support of students with disabilities at institution of higher learning in South Africa: a case study of the University of Venda - Mantsha, Tshifhiwa Rebecca (My University, 2016)
For the past two to three decades, there has been a large influx of students with disabilities into institutions of higher education worldwide. In South Africa, in these past three decades, records of intake of students with disabilities were not recorded as services and support of this kind were not institutionalised. Within this transformation process, which involved including previously under-represented groups, institutions of higher learning are currently facing challenges of what kind of educational support to offer to students with disabilities, in order to help them to succeed academically. This study investigated the educational support offered to students with disabilities at the University of Venda (UNIVEN) as experienced by the students themselves. The study, therefore, gives an insider perspective. The study followed a qualitative research approach, and used classroom observations, document analysis and focus group interviews to collect data. Ten students with various disabilities participated in the study. The findings of this study reveal that there are some degrees of support that UNIVEN offers. However, some gaps to meet students educational needs still exist. These gaps include lack of information about the programmes that UNIVEN is offering, physical infra-structure barriers and lack of disability knowledge. This study recommends the establishment of a forum in which students with disabilities can discuss and address their educational needs on campus. Other recommendations include the following: lecturers’ training, disability awareness, the installation of an online interactive portal to increase communication between students and the university, and an online survey measuring lecturers’ attitudes and knowledge. The study suggests that future research could include factors that predict graduation rates among students with disabilities. Key words: Educational support, Disability unit, Medical Model of disability, Social model of disability.
Thesis (Ph. D. (Educational Psychology)) -- University of Limpopo, 2016
Keywords: Students with disabilities; University students; University of Venda -- Students; Handicapped -- Services for; Students with disabilities; College students with disabilities; Learning disabled (Higher); People with disabilities -- Education (Higher)